Xq28 duplication including MECP2 in six unreported affected females: what can we learn for diagnosis and genetic counselling?. Issue 4 (16th February 2017) - El Chehadeh, S.; Touraine, R.; Prieur, F.; Reardon, W.; Bienvenu, T.; Chantot‐Bastaraud, S.; Doco‐Fenzy, M.; Landais, E.; Philippe, C.; Marle, N.; Callier, P.; Mosca‐Boidron, A.‐L.; et al.
Abstract : Duplication of the Xq28 region, involving MECP2 (dupMECP2), has been primarily described in males with severe developmental delay, spasticity, epilepsy, stereotyped movements and recurrent infections. Carrier mothers are usually asymptomatic with an extremely skewed X chromosome inactivation (XCI) pattern. We report a series of six novel symptomatic females carrying a de novo interstitial dupMECP2, and review the 14 symptomatic females reported to date, with the aim to further delineate their phenotype and give clues for genetic counselling. One patient was adopted and among the other 19 patients, seven (37%) had inherited their duplication from their mother, including three mildly (XCI: 70/30, 63/37, 100/0 in blood and random in saliva), one moderately (XCI: random) and three severely (XCI: uninformative and 88/12) affected patients. After combining our data with data from the literature, we could not show a correlation between XCI in the blood or duplication size and the severity of the phenotype, or explain the presence of a phenotype in these females. These findings confirm that an abnormal phenotype, even severe, can be a rare event in females born to asymptomatic carrier mothers, making genetic counselling difficult in couples at risk in terms of prognosis, in particular in prenatal cases. Abstract :